Energy-efficient homes: Effects on poverty, environment and comfort - Vincent P. Roberdel; Ioulia V. Ossokina; Vladimir A. Karamychev; Theo Arentze (Tinbergen Institute, 2023)
Energy efficiency improvements in low income housing are increasingly used as a policy instrument to alleviate poverty. Our paper shows that this may come at the expense of reduced environmental benefits. We follow 125,000 Dutch low-income households during eight years and exploit a quasi-experimental policy that diminished the heat losses in their homes. We pay specific attention to the policy effects at the very left tail of the income distribution. While the average after-policy reduction in natural gas consumption for heating amounts to 22%, the poorest only save 16%. We build and calibrate a microeconomic model explaining this pattern from substitution between thermal comfort and other goods, and use it to compute welfare trade-offs of the policies.
Keywords: D12; Q4; Q48; Q5; 330; Energy-efficient homes; Social housing; Poverty; Quasi-experiment; Retrofit; Welfare effects